Multiple control levels of root system remodeling in arbuscular mycorrhizal symbiosis - Paszkowski, Uta; Gutjahr, Caroline (Frontiers in Plant Science, 2013)
In nature the root systems of most plants develop intimate symbioses with Glomeromycotan fungi that assist in the acquisition of mineral nutrients and water through uptake from the soil and direct delivery into the root cortex. Root systems are endowed with a strong, environment-responsive architectural plasticity that also manifests itself during the establishment of arbuscular mycorrhizal (AM) symbioses, predominantly in lateral root proliferation. In this review we collect evidence for the idea that AM induced root system remodeling is regulated at several levels: by AM fungal signaling molecules and by changes in plant nutrient status and distribution within the root system.